Production and processing of pineapple - Adabe, K. Edoh; Hind, Salama; Maïga, Abdou (Technical Centre for Agricultural and Rural Cooperation, 2016)
A herbaceous, perennial and heliophile plant, and a member of the Bromeliaceae family, the pineapple has significant nutritional, commercial and industrial potential. Mainly grown for its fruit, the pineapple can be consumed fresh, dried or processed into preserves, drinks or vinegar. This manual on the production and processing of pineapples is intended for small and medium sized pineapple producers and processors, as well as extension agents in this subsector. While taking account of the extensive agricultural, pedological and climatic diversity of the world’s pineapple-growing regions, it is important to give a broad outline of the traditional pineapple production process, at the same time recommending some pesticides and fertilisers that can be used in the production process.